Wage differentials between the metropolitan regions of Belo Horizonte and Salvador: a discussion based on the blinder-oaxaca decomposition - Cirino, Jader Fernandes; de Lima, João Eustáquio (Revista Econômica do Nordeste, 2016)
This study quantifies and explains the difference in hourly wages between the metropolitan regions of Belo Horizonte (RMBH) and Salvador (RMS). The choice of these two regions was due to the interest inverifying how the difference of economic dynamism between the regions would impact the labor market is return. The method employed was the Blinder-Oaxaca decomposition. As expected, the results showed that the income per hour in RMBH were on average higher than those found in the RMS, due to greater economic concentration and agglomeration of the former region when compared to the latter.